The Scientific Foundations of Modern Sterilization Processes and Their Role in Microbiological Safety (Texas Journal of Agriculture and Biological Sciences, 2025)
This article provides an expanded theoretical overview of modern sterilization processes, emphasizing their scientific foundations, molecular mechanisms, and critical role in microbiological safety. Sterilization is examined as a complex, interdisciplinary system integrating microbiology, chemistry, physics, and biotechnology. The paper discusses the resistance mechanisms of microorganisms—particularly bacterial spores—and the ways in which physical, chemical, and radiation-based sterilization methods overcome such resistance. The study highlights the importance of process validation, biological indicators, and emerging low-temperature and plasma-based sterilization technologies. The article concludes that sterilization represents a key component of scientific research integrity, clinical safety, and modern biotechnological manufacturing.